Standard Handbook for Aerospace Engineers, Second Edition - Agrawal, Brij N.; Platzer, Max F. (McGraw-Hill Education, 2018)
A single source of essential information for aerospace engineers. This fully revised resource presents theories and practices from more than 50 specialists in the many sub-disciplines of aeronautical and astronautical engineering?all under one cover. Standard Handbook for Aerospace Engineers, Second Edition, contains complete details on classic designs as well as the latest techniques, materials, and processes used in aviation, defense, and space systems. You will get insightful, practical coverage of the gamut of aerospace engineering technologies along with hundreds of informative diagrams, charts, and graphs.